Religião, alienação e emancipação: a filosofia da autoconsciência de Bruno Bauer e seus desdobramentos - Samuel Franca Alves (2015)
This paper aims to explain, through a systematic approach, how Bruno Bauer understands the phenomenon of alienation from which he considers one of its specific and basic forms of manifestation, namely, the religious consciousness. The basis on which this philosopher sought to raise his thought is a reinterpretation of the Hegelian system, specifically focused on understanding the experience of consciousness in the Phenomenology. For Bauer, the figures of the Absolute Spiritand the World Spirit are metaphors that represent human self-consciousness, and the education process described by phenomenology should culminate in the elevation of the individual to this selfconsciousness, by which he recognizes himself endowed with a universality posed by his belonging to humanking, creator of himself and his world. The religious consciousness has, through the ideaof a universal substance, permitted overcoming the isolation in which consciousness was. But becomes the biggest obstacle that the man raised against himself and his own freedom by creating religious sects, that claims to contain in its worship and dogmas an absolute truth and so operates a alienation of all human powers in the figure of superhuman and superterrestrial deities. As a result, man is taken to establish a denial relation to the real world, waiting for a post mortem surrender.The secularization of state is then seen as conditio sine qua non for it to fulfill the role of its own: represent the reconciliation between the subjective and the objective will, providing mankind a rational social existence, in which the law and the institutions appears as the positive reality of freedom. However, it's not possible to expect the Christian state simply becomes secular state, and then provide men his freedom, since this same state is the unity of society. Appears so the characterof Critical Philosophy, which aims to be not only apprehension of reality, but instrument of its transformation, to lead the individual consciousness to criticism of their own condition and elevation to self-consciousness.